The effect of the private sector on geographic distribution of public sector physicians in Turkey, 1990-2000 - Bilir, Ayça. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The availability and distribution of physicians is an important indicator of the strength of a health system and is highly associated with mortality rates and life expectancy. The purpose of this study is to determine the factors affecting the public sector physician supply in Turkey with an emphasis on the impact of private hospitals. The change in the physician supply at city-level from 1990 to 2000 is regressed on the number of private and public hospital beds, certain socio-economic variables and market area characteristics. Considering that the response to private hospitals could differ across physicians with different characteristics, the analysis is repeated using 1) specialists vs practitioners, 2) physicians working for different types of hospitals (namely Ministry of Health, SSK and university hospitals). The effect of private hospital capacity is found to be significant and positive for specialists, whereas it is negative for practitioners. There is a significant and positive correlation between the private bed numbers and the supply of specialists working in MoH and university hospitals, but it does not seem to affect the SSK hospitals. Finally, the ten year period is divided into two 5-year periods to detect the effect of the change in obligatory service law in 1995 on the distribution of physicians.
Keywords: Medical care -- Turkey.; Medical policy -- Turkey.